Rapid tool based on a food environment typology framework for evaluating effects of the COVID-19 pandemic on food system resilience - Ahmed, Selena (Food Secur, 2020)
The coronavirus disease 2019 (COVID-19) and associated mitigation measures are highlighting resiliency and vulnerability of food systems with consequences for diets, food security, and health outcomes. Frameworks and tools are called for to evaluate impacts of the COVID-19 pandemic as well as identify entry points for implementing preparedness efforts. We support it is critical to adopt a food environment typology framework based on the different types of food environments that people have access to in order to examine how their relationship with food environments shift with disruptions such as COVID-19 and, ultimately impact diets and food security. Here, we provide an overview of applying a food environment typology framework for developing and implementing a rapid tool to evaluate the effects of COVID-19 on interactions people have with their food environments. This tool was developed on the basis of a preliminary case study with smallholder farmers in China that generated a set of key hypotheses. We modified the tool in order to be applicable to diverse contexts in low-, middle-, and high-income countries. Other researchers can implement the rapid tool presented here during times of COVID-19 as well as other disruptions towards identifying barriers and opportunities for enhancing food system resilience. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12571-020-01086-z) contains supplementary material, which is available to authorized users.